Mechanically and chemically robust molybdenum carbide-graphene hybrid conductors. (15th June 2021) - Bae, Garam; Kim, Jeonghui; Yoon, Yeoheung; Song, Da Som; Kim, Minji; Jeon, Choelho; Song, Wooseok; Myung, Sung; Lim, Jongsun; Lee, Sun Sook; Jung, Ha-Kyun; Park, Chong-Yun; et al.
Abstract: Although transition metal carbides (TMCs) exhibit intriguing physical and chemical properties, a central issue for multifaceted applications based on TMC materials is to meet a large-scale and reliable synthetic route of air-stable TMC materials. Here, the primary aim is to address the issues by synthesizing Mo2 C encapsulated with multilayer graphene coral-like nanostructure. The oxidation stability of Mo2 C can be effectively compensated by the complementary hybridization of multilayer graphene, which serves as a perfect chemical barrier. Large-scale graphene/Mo2 C can be readily synthesized on commercial Mo foils by surface-oxidation-mediated chemical vapor deposition. Explicit structural and chemical evaluation was implemented to explore the structural and chemical manipulation of Mo2 C by selecting the starting material (Mo or MoO3 ). Differences in the thickness of the oxide layers on the Mo surface led to structural and material diversities for the formation of Mo2 C with nanogranular and graphene/Mo2 C coral-like nanostructures. The capability of graphene/Mo2 C for applications in nanostructured electrodes and heaters was validated by its extraordinary electrical conductivity, substantial enhancement in chemical durability and mechanical flexibility, and outstanding performance of deformable heaters. Graphical abstract: Image 1